Sensory-motor perception -balance perception- and its relationship to motor creativity to the children to Preparatory classes. - kherchi salim (sports creativity, 2025)
The search aimed to identify the sensory-motor perception, the creativity, and its components. With Preparatory, classes5 years, either second goal was identify the relationship between balance perception and motor creativity in Preparatory classes. So, The researcher used the descriptive method style relational on sample of 30 student from school "Aban ramdan", years 2018/2019, and used test of balance from test of ‘Dagton’ sensory perception and test of ‘Weyrek’ the motor creativity, and it’s components on the sample, were treated results statistically using the statistically system the ‘SPSS’ The most important conclusion: 1- There is no significant static correlation between the perception of balance and the components of motor creativity. 2- There are no statistically significant differences in motor creativity to the sex variable. 3- No statistically significant difference in the balance the sex variable.